MOLECULAR DOCKING STUDY OF PINOSTROBIN INCLUSION COMPLEXES WITH Β-CYCLODEXTRIN AND HYDROXYPROPYL-Β-CYCLODEXTRIN - Hanum Dea Atila; I Gusti Made Sanjaya; Muhammad Ikhlas Abdjan (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
Pinostrobin is the main flavonoid compound in Boesenbergia rotunda rhizomes known to have various biological activities, but its water solubility is very low, which can limit its pharmaceutical applications and reduce bioavailability. β-Cyclodextrin (β-CD) is often used as an inclusion complexing agent to improve the solubility and stability of hydrophobic compounds. This study comparatively investigated the molecular interactions of pinostrobin with β-cyclodextrin (β-CD) and its derivative (hydroxypropyl-β-cyclodextrin (HP-β-CD)) through density functional theory (DFT) calculations and molecular docking simulations to identify the more formed inclusion complexes. Docking results showed spontaneous inclusion complex formation for both cyclodextrins. HP-β-CD showed slightly stronger binding affinity (−5.9 kcal/mol) than β-CD (−5.7 kcal/mol). These findings indicate that HP-β-CD provides a more stable inclusion complex than native β-CD and is a more promising carrier for improving the solubility and pharmaceutical performance of pinostrobin.